A Cross-Sectional Study of the Histopathological correlation with serum Level of Carbohydrate Antigen-125 in Different Forms of Ovarian Cancer - Roquiya Begum; Suhail Ahmad; Ram Binay Sinha; Farhan Usmani (Asian Journal of Medical Research, 2019)
Background: Ovarian cancer is a common malignancy of the female reproductive system. Tumor markers serve as tools in the diagnosis of the disease. The aim of the present study was to determine the diagnostic value of sera levels of carbohydrate antigen-125 (CA-125)and correlate its level with the histopathological findings of the ovarian mass specimen. Subjects and Methods:The sera were measured using an electrochemoluminescence technique on 200 individuals (100 patients with ovarian cancer, and 100 patients as control). Results:The results showed that levels of CA?125 in the sera of the malignant ovarian neoplasm were significantly higher than those of the control groups. In the malignant epithelial cancers, the highest rise was seen in serous Cyst adenocarcinoma, metastatic carcinoma and then mucinous cyst adenocarcinoma, respectively.Conclusion: In conclusion, the results showed that the serum level of CA-125 is important indicators in the diagnosis of ovarian cancer despite its limited sensitivity in early stage of disease and its inadequate specificity for malignancy.